Cardiovascular fitness and cardiovascular risk factors among obese men and women aged 58 years and older, in Portugal - Araujo, Romulo [UNESP]; Edilson Serpeloni, C.; Vaz R, Enio R.; Renata Selvatici Borges, J.; Silva, Analiza Monica; Minderico, Claudia Sofia; Rocha, Paulo Manuel; Santa-Clara, Helena; Baptista, Fatima; Sardinha, Luis Bettencourt (Soc Médica Santiago, 2012)
Background: A better physical fitness may have survival advantages in adults. Aim: To analyze the relationship between cardiorespiratory fitness and cardiovascular risk factors among obese subjects aged 58 years and older. Material and Methods: Cardiorespiratory fitness using the six-minute walk test, body composition by dual-energy x-ray absorptiometry and blood pressure were measured in a non-representative sample of 76 obese Portuguese subjects aged 58 to 87 years (55 women). Participants were stratified in tertiles of walking capacity according to the six-minute walk test. Results: Six minutes walk test results were negatively correlated with percentage body fat (r = -0.28; p = 0.012) and systolic blood pressure (r = -0.23; p = 0.045). Participants located in the lowest tertile for the six minutes walk test had an odds ratio of 4.34 (95% confidence intervals: 1.02-18.43) for elevated blood pressure. Conclusions: A lower six minutes walk test result is associated with a higher risk for high blood pressure. (Rev Med Chile 2012; 140: 1164-1169).

Antecedentes: Una mejor condición física se asocia a mejor sobrevida en adultos. Objetivos: Estudiar la relación entre condición física y factores de riesgo cardiovascular en obesos mayores de 58 años. Material y Métodos: Se midió la capacidad cardiorrespiratoria mediante la prueba de caminata de seis minutos, composición corporal mediante densitometría de doble fotón y presión arterial en una muestra no representativa de 76 portugueses de 58 a 87 años (55 mujeres). Los participantes se estratificaron en terciles de acuerdo a los resultados de la prueba de seis minutos. Resultados: Los resultados de la prueba de caminata de seis minutos se correlacionaron negativamente con el porcentaje de grasa corporal (r = -0,28; p = 0,012) y presión sistólica (r = -0,23; p = 0,045). Los participantes ubicados en el tercil más bajo de la prueba de caminata de seis minutos tenían una razón de riesgo para hipertensión arterial de 4,34 (intervalos de confianza de 95%: 1,02- 18,43). Conclusiones: Una prueba de caminata de seis minutos con bajos resultados se asocia a un mayor riesgo de hipertensión arterial.
Asociación entre el test de caminata de seis minutos y factores de riesgo cardiovascular en portugueses obesos
Keywords: Aged; Hypertension; Obesity; Physical fitness